2009
DOI: 10.1007/s11668-009-9213-6
|View full text |Cite
|
Sign up to set email alerts
|

High Strength Engineering Fasteners: Design for Fatigue Resistance

Abstract: One of the most frequently encountered causes of failure in engineering fasteners is fatigue. Typical locations for the fatigue of fasteners are the stress concentrations represented by the head to shank fillet, the first engaged thread and the thread runout. These locations are examined in relation to design rules known for over 60 years to be effective in reducing the stress concentration effect, but seldom used in engineering bolts, despite their relative simplicity. These design rules are also examined in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Indeed, despite what was reported in the literature regarding the most frequent site of fatigue failure in fasteners, i.e. the first thread [7,24], it was experimentally observed by the manufacturer that a sub-head connecting radius of less than 1 mm causes a fatigue failure that occurred at the fillet.…”
Section: Initial Campaignmentioning
confidence: 94%
See 1 more Smart Citation
“…Indeed, despite what was reported in the literature regarding the most frequent site of fatigue failure in fasteners, i.e. the first thread [7,24], it was experimentally observed by the manufacturer that a sub-head connecting radius of less than 1 mm causes a fatigue failure that occurred at the fillet.…”
Section: Initial Campaignmentioning
confidence: 94%
“…Among the several rotation-symmetrical components that can take advantage of the deep rolling treatment, high loaded fasteners are typical examples, since, owing to the nature of their application, they frequently operate under cyclic loads, thus making fatigue the most frequent failure mode [6]. Despite this aspect, not so many works in literature systematically explore the design issues of fasteners with the aim of addressing their resistance against fatigue failure [7]. As a general rule, engineers often select fasteners based on their specifications for strength (tensile or yield strength) without specifically considering fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…b, c -were proposed by authors [9] as an optimal design for an axial load. loads are variable and the preload is constant.…”
Section: Methodsmentioning
confidence: 99%
“…Authors focused on the reduction of the thread stresses in order to maximise lifetime of the bolts when cycling loading is presented. Taking into account the topic of the presented work, the most important is the article of O'Brien's and Metcalfe [9], in this paper the authors showed a reviewed of existing knowledge of the bolt/nut design for preventing fatigue failures. The article was an inspiration for starting the presented project.…”
Section: Literature Reviewmentioning
confidence: 99%
“…So far, many professionals and scholars have proposed reasonable design methods for thread structures and achieved good results in practice. O'Brien and Metcalfe (2009) proposed the bolt structure improvement principle and method to improve the fatigue life of the bolt; Fukuoka (1997) found that the radius of the art at the root of bolts greatly affected the magnitude and distribution of the root stress; Chen et al (2010) used the FEM to analyze the influence of tooth type, pitch and other factors on the force distribution of the bolt, and the photoelastic test was carried out. The structure of the photoelastic test and the finite element results were compared to verify the consistency of the two.…”
Section: Introductionmentioning
confidence: 99%